Research on evolution law and mathematical model of pore fracture evolution in vertical slot coal under stress and gas relief - Wang, Zhonghua; Guo, Zhongping; Sun, Dongling; Zhang, Yongjiang; Yang, Huiming (Frontiers in Earth Science, 2025)
In order to solve the global problem of prevention and control of coal and gas outburst disaster dominated by ground stress in deep coal seam. It is found that hydraulic slotting and gas extraction have double pressure relief for coal seam horizontal stress and gas. The double pressure relief coefficient is proposed. Mechanical seepage experiments of coal samples with different double pressure relief coefficients (β = 0.5, 1.0, 1.5) were designed. The evolution mechanism and mathematical model of macro - fine - micro structure of coal seam fracture under the action of stress and gas relief are obtained. The results show that: with the increase of double pressure relief coefficient β, the fracture of vertical slot coal has a tendency to gradually weaken, and the fracture changes from tension failure to split failure, and from covering the whole coal body to the upper part of the coal. The macro-fracture plays a more dominant role than the micro fracture. When β = 1.0 (△σ = △P), the macro fracture is the most developed. When β = 0.5 (△σ = 0.5△P), the meso-fracture is the most developed. Before and after the test, the proportion of micropores and small pores is the largest, the proportion of large pores is the second, and the proportion of middle pores is the smallest. The proportion of cumulative fracture volume increased gradually and the growth rate was similar. It is found that there is a quadratic or cubic functional relationship between the fracture parameters of vertical slot coal under the double pressure relief coefficient β. It is found that there is a logarithmic function relationship between pore size and cumulative volume ratio. The research results provide a scientific basis for double pressure relief and permeability improvement of coal seam stress and gas, efficient extraction and effective outburst prevention.